“EZZLEBLOCK”: Eco Puzzle Brick Kedap Air Sistem Interlock dengan Substitusi Limbah Plastik - Fajar Kurniawan; Alan Victor Zuhruf Ashari; Shifa Fauziyah; Riza Susanti (Jurnal Sipil dan Arsitektur, 2024)
In Indonesia, the accumulation of plastic waste must be addressed immediately because the amount will increase over time. In 2022, the total amount of plastic waste produced in Indonesia will reach 9.13 million tons, making Indonesia the country with the 5th most significant amount worldwide. The large amount of plastic waste produced must be dried through proper processing. Because if not, plastic waste will continue to pile up and cause various problems. Meanwhile, the high growth of infrastructure in Indonesia has caused an increase in demand for construction materials, one of which is cement. To meet this demand, the cement manufacturing industry exploits natural resources on a large scale, which will hurt nature. Apart from that, the cement fabrication process also causes problems in the form of waste and produces carbon dioxide gas, which pollutes the air. This research was carried out to make bricks made from plastic and sand with an interlock system to reduce environmental negative impacts. And to find out the effect of ezzleblock composition on brick quality. This research planned to use experimental methods by collecting essential materials car, trying out the production process, and testing them in the laboratory to obtain data. Using plastic waste and sand as materials for making ezzleblocks, it is planned to create a high-quality interlock brick with dimensions of (300x120x150) mm. Its high compressive strength, low air absorption capacity, and sturdy construction demonstrate this.